Co-inoculation of biochar and arbuscular mycorrhizae for growth promotion and nutrient fortification in soybean under drought conditions - Jabborova, Dilfuza; Annapurna, Kannepalli; Azimov, A.; Tyagi, Swati; Pengani, Kedharnath Reddy; Sharma, Prakriti; Vikram, K. V.; Poczai, Peter; Nasif, Omaima; Ansari, Mohammad Javed; Sayyed, R. Z. (Frontiers in Plant Science, 2022)
Drought is significant abiotic stress that affects plant growth, development, and yield in many crops. This study investigated the effect of biochar and arbuscular mycorrhizal fungi (AMF) on growth, root morphological traits in soybean, and soil enzyme activities under drought stress. The effect of biochar and AFM on growth and root morphological traits in soybean and microbial biomass, AMF spores number, and activities of the soil enzymes was studied under drought conditions in pot experiments in a net house. Treatments included: control (soil without biochar), biochar alone, AFM alone, and dual applications of biochar and AMF. After forty days, plant height, nodule number, dry shoot weight, and dry root weight were measured. Root morphological traits were analyzed using Win RHIZO software (Régent Instruments, Québec, Canada). Drought stress negatively affected soybean growth, root morphological traits, chlorophyll content, microbial biomass, and soil enzymes. Biochar and AMF individually increase significantly plant growth (plant height, root dry weight, nodule number), root morphological traits (total root length, root volume, projected area, root surface area, root diameter), total chlorophyll content, and nitrogen content in soybean as compared to the control under drought stress. Dual applications of biochar and AMF significantly enhanced plant growth parameters, root morphological traits, total chlorophyll, and nitrogen contents in soybean compared to control under drought conditions. However, combined with biochar and AMF positively affects microbial biomass, AMF spores number, and soil enzyme activities in water stress conditions. Dual applications of biochar and AMF increase microbial biomass by 28.3%, AMF spores number by 52.0%, alkaline phosphomonoestrase by 45.9%, dehydrogenase by 46.5%, fluorescein diacetate by 52.2%, activities as compared to the control under drought stress. Combined with biochar and AMF enhance plant growth, root morphological traits in soybean and soil enzyme activities, and water stress tolerance. Dual applications with biochar and AMF benefit soybean cultivation under water stress conditions.